Isolation and Characterization of Antibiotic Resistant Bacteria from Swiftlet Feces in Swiftlet Farm Houses in Sarawak, Malaysia - Samuel, Lihan; Leong, Sui Sean; Ling, Teck Yee; Chia, Hwa Chuan; Lim, Chan Koon (Indonesian Society for Microbiology (Secretariat PERMI), 2013)
There is a growing concern on the occurrence of antimicrobial resistance. Development of multiple antibiotic resistant bacteria has overtaken new drug development and threatened the patients with untreatable infections. This study was conducted to isolate and characterize the antibiotic resistant bacteria from swiftlet farm houses located in various places including Kota Samarahan, Semarang, Saratok, Betong, Sarikei, Sibu, Sepinang, Maludam, Miri, and Kuching inSarawak, Malaysia.Five fecessamples were collected randomly from each site. One gram of the fecessample was diluted in 9 mLof 0.85% normalsaline solution. The diluted sample was plated on TrypticaseSoy agar plates and incubated at 37±1 °C for 24 h. A total of 500 bacteria isolates were then identified using 16S rRNA analysis method. Disc diffusion method was then used to confirm the resistant phenotypes of these isolates. The results showed that the means of the bacterial colony count were significantly -1 different (p<0.05) from one another, with the highestlog CFU g (9.22±0.72) found in KotaSamarahan and the 10 -1 lowest log CFU g (6.03±0.62) in Betong. Besides, the isolated bacteria were identified as 96% Gram positive 10 bacteria and 4% Gram negative bacteria. The isolated bacteria were highly resistant to penicillin G (36.80±23.87%), ampicillin (28.60±17.13%), and rifampicin (16.90±13.70%). Thus, swiftlet feces are good reservoirfor a range of antibiotic resistant bacteria whichmay pose a potential health hazard to human.